(untitled) (Research, Society and Development, 2022)
Objective: The objective of this study was to evaluate the levels of trait-anxiety and state-anxiety of nursing students at a university center during the Covid-19 pandemic. Methodology: This is a cross-sectional, quantitative, qualitative and convenience sampling study. We used the Trait Anxiety and State Anxiety- STAI (Spielberger, Gorsuch and Lushene, 1970) questionnaire as a research instrument, a questionnaire composed of two Likert scales where the response varies from 1 to 4. Results: There was adherence to the research of 138 students of the nursing course, where we concluded that students from Group 1 and Group 2 had higher levels of state anxiety and trait anxiety than Group 3. Conclusion: There was an exacerbation in the anxiety levels of nursing students due to the proposed changes in the teaching, becoming hybrid.